PENGARUH CONDITIONING THERAPY DAN MODEL THERAPY BERBASIS OBSERVATIONAL LEARNING THEORY TERHADAP PERILAKU ANAK PRA SEKOLAH DALAM MENGGOSOK GIGI - ULVA NOVIANA (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2018)
Children usually have a tendency to clean teeth (brushing teeth) only in part - certain parts of it. Cleaning is not good because it is more plaque attached and will become tartar (Nitisa, 2012). Preliminary study results showed that the low habits of children in brushing their teeth. The purpose of this study was to analyze the differences in behavior in brushing teeth between the group given condiotioning therapy and therapy models in TK Nurul Ulum Junok Bangkalan. This study used research methods quasy - Experiment. The independent variable is the conditioning therapy and therapy models. The dependent variable is the behavior of brushing teeth. The population in this study were 50 respondents. Samples taken were 32 respondents and divided into groups of conditioning therapy and group therapy models. Instruments in this study were questionnaires and SOP. The statistical test used Paired t Test with α ≤ 0.05. The results showed that there are differences in the behavior of brushing teeth before and after conditioning therapy with a p value of 0.000 <0.05 and there are a difference in behavior brushing teeth before and after therapy models with p value of 0.000 <0.05. Statistical analysis using Independent t-test showed a significance value p value of 0.894. It concluded that there was no significant difference between the behavior of brushing teeth group given conditioning therapy and therapy models. Based on the research results, it is expected for the parents can apply conditioning therapy and model therapy to improve tooth brushing habits.